"An analytical study of The New Urbanism in the urban suburbs (Journal of Planner and Development, 2022)
The research deals with the concept of a New Urbanism as an urban development strategy in the suburbs of cities or in its centers that are affected by pedestrian-oriented design and the possibility of walking, as well as integrating economic classes through the diversity of housing and its costs, and this works to facilitate access to jobs and services while providing more diverse neighborhoods and reducing the use of cars , As designing separate houses in the suburbs and increasing car trips poses a threat to the environment and the quality of urban life, and thus the new urban provides a good strategy for developing and renewing cities and suburbs. The concept of the new urbanism has become in the current period a comprehensive concept for the reformulation of cities at the macro level, hence the focus of general research to present a specialized study on the concept of a new urbanism in urban cities and to address its principles and explain its characteristics and the most important theories related to it and study research related to its application in various cities of the world And drawing positive and negative points and ways to achieve it and how to deal with the changes that occur in cities through the new urban. To address the focus of the private research, the proposals and studies that dealt with different directions of the research topic were reviewed, and from here the research problem emerged "the lack of clarity of the new urbanism role as a strategy for developing urban suburbs and controlling random urban spread" and the goal of the research was determined on the basis of it "application of the new urbanism concept in the development of urban suburbs and controlling indiscriminate urbanization. In this research, a comprehensive theoretical framework has been built for the concept of the New Urbanism and the ways to apply it, and the research was based on achieving its goals and addressing the research problem based on the following hypothesis, which states that "the process of developing the outskirts of the city will be achieved through the application of various New Urbanism principles." A district of Baghdad that suffers from urban problems was randomly chosen for its growth and development, which is the city of Al-Husayniyah, for the purpose of validating the hypothesis and the possibility of its application to solve the problems of Iraqi cities. Where a field survey was conducted for the area and to see the problems that it suffers from, and a poll was conducted for both the people of the city and slum dwellers to reach a broader understanding of people’s vision and acceptance of them to apply the New Urbanism concepts. The proposed solution is based on realistic analysis and possible solutions that can be applied in practice.